2018
DOI: 10.1152/ajpendo.00272.2018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms responsible for reduced erythropoiesis during androgen deprivation therapy in men with prostate cancer

Abstract: Androgen deprivation therapy (ADT) is a mainstay of treatment for prostate cancer (PCa). As androgens stimulate erythropoiesis, ADT is associated with a reduction in hematocrit, which in turn contributes to fatigue and related morbidity. However, the mechanisms involved in ADT-induced reduction in erythropoiesis remain unclear. We conducted a 6-mo prospective cohort study and enrolled men with PCa about to undergo ADT (ADT-Group) and a control group of men who had previously undergone prostatectomy for localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Similar effects were observed in clinical trials with healthy or anemic men [150,151,152] and men with type 2 diabetes and concurrent hypogonadotropic hypogonadism [153]. Conversely, androgen deprivation therapy reduced erythropoiesis and increased hepcidin in men with prostate cancer [154]. These findings suggest that testosterone could be valuable for the treatment of AI; however, cardiovascular adverse effects associated with testosterone administration limit its clinical applications [155].…”
Section: Inhibitors Of Hepcidin Expressionmentioning
confidence: 56%
“…Similar effects were observed in clinical trials with healthy or anemic men [150,151,152] and men with type 2 diabetes and concurrent hypogonadotropic hypogonadism [153]. Conversely, androgen deprivation therapy reduced erythropoiesis and increased hepcidin in men with prostate cancer [154]. These findings suggest that testosterone could be valuable for the treatment of AI; however, cardiovascular adverse effects associated with testosterone administration limit its clinical applications [155].…”
Section: Inhibitors Of Hepcidin Expressionmentioning
confidence: 56%
“…androgen deprivation therapy for prostate cancer has recently been shown to be associated with a decrease in leukocyte count. 14 However, there are no randomized trial data on the effects of exogenous testosterone on circulating leukocytes and platelets. Because of the known association of increased leukocyte [15][16][17][18] and platelet counts [19][20][21] with cardiovascular and thromboembolic risk, these findings, if confirmed in human studies, could affect the safety of testosterone treatment.…”
Section: Suppression Of Endogenous Testosterone Secretion Throughmentioning
confidence: 99%
“…The present study found that EPO reduced ZFP423 expression and adipocyte formation from CKO-CPC, suggesting that lower EPO levels in CKO hearts may further promote the shift from endothelial to adipocyte differentiation in CKO-CPC. So far, there is no evidence for a sex-specific regulation of EPO since EPO blood levels in patients undergoing androgen deprivation therapy remained unchanged [ 51 ].…”
Section: Discussionmentioning
confidence: 99%